2018
DOI: 10.1088/1361-665x/aac8ad
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of magnetic plucking dynamics in a frequency up-converting piezoelectric energy harvester

Abstract: The paper reports on numerical-experimental analysis of magnetic plucking, which is commonly applied for contactless mechanical frequency up-conversion in vibration energy harvesters with the aim of enhancing power output and efficiency under low-frequency (non)periodic excitations. In-plane magnetic plucking is examined thoroughly by treating it as a specific type of transient excitation that is governed by temporal characteristics of complex-shaped magnetic force impulses. The study focuses on systematic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Moreover, the magnetometers registered magnetic field in the middle of the gap between the magnets, while magnetic forces that deflect the transducer, act directly on the driven magnet. Our previous study demonstrated that the measured tramp(Bx) and tramp(By) values are higher approximately by 10% with respect to the actual magnetic forces [16]. However, it is noted that these quantitative discrepancies do not have consequential effect on the results of this research work, particularly in terms of relationships between governing temporal parameters (ramping times, rise times, periods).…”
Section: Methodsmentioning
confidence: 68%
See 3 more Smart Citations
“…Moreover, the magnetometers registered magnetic field in the middle of the gap between the magnets, while magnetic forces that deflect the transducer, act directly on the driven magnet. Our previous study demonstrated that the measured tramp(Bx) and tramp(By) values are higher approximately by 10% with respect to the actual magnetic forces [16]. However, it is noted that these quantitative discrepancies do not have consequential effect on the results of this research work, particularly in terms of relationships between governing temporal parameters (ramping times, rise times, periods).…”
Section: Methodsmentioning
confidence: 68%
“…Digital oscilloscope PICO 6403 with software PicoScope 6 were used to capture and process signals of the magnetometers and the transducer, which was connected to the matched load resistor RML. All the measurements were made with P-VEH operating in the impulsive excitation regime, which means that the total transient response is largely dominated (energywise) by free vibrations characterized by a single (natural) frequency fn = 80 Hz (more than 90 % of electrical energy is generated during free vibrations under impulsive excitation conditions [16]). Therefore, value of matched load resistance may theoretically estimate as RML = 1/2fnCPT = =9.95 kΩ (CPTcapacitance of the transducer).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnetic force can be used as an intermediate driving force to drive the vibration of the piezoelectric beams, which convert the vibration energy into electrical energy [ 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ]. It is better to harvest the energy of rotational motion.…”
Section: Magnetic Plucking Energy Harvestersmentioning
confidence: 99%